Digital Material Tracing New Media in Everyday Life and Technology - Raessens, Joost; van den Boomen, Marianne; Lammes, Sybille; Lehmann, Ann-Sophie; Schäfer, Mirko Tobias (MediaMatters, 2009)
Three decades of societal and cultural alignment of new media have yielded a host of innovations, trials, and problems, accompanied by versatile popular and academic discourse. New Media Studies crystallized internationally into an established academic discipline, and this begs the question: where do we stand now? Which new questions are emerging now that new media are being taken for granted, and which riddles are still unsolved? Is contemporary digital culture indeed all about 'you', the participating user, or do we still not really understand the digital machinery and how this constitutes us as 'you'? The contributors to the present book, all employed in teaching and researching new media and digital culture, assembled their 'digital material' into an anthology, covering issues ranging from desktop metaphors to Web 2.0 ecosystems, from touch screens to blogging and e-learning, from role-playing games and cybergothic music to wireless dreams. Together the contributions provide a showcase of current research in the field, from what may be called a 'digital-materialist' perspective.